Australian no-body homicides: Exploring common features of solved cases. (August 2019) - Ferguson, Claire; Pooley, Kamarah
Abstract: Offenders successfully disposing of a homicide victim's body creates challenges to the criminal justice process, yet no research literature exists on no-body homicide cases. We explored 25 solved homicides in Australia where no part of the victim's body was recovered. Coroners' findings, case law, and media reports from 1983 to 2017 were examined qualitatively and descriptively. Features of the cases differed based on whether the homicide was related to organized crime, serial sexual offences, or domestic violence. Challenges posed by each type of case are discussed and opportunities for solving these cases are examined. Highlights: Very little is known about homicides involving permanent body disposal. No-body homicides appear to differ based on offender motive and experience. Body disposal in organized crime murders have not been studied previously. Solved by confessions, trophies, and showing offender lies with physical evidence.